Views and Experiences of South Australian Midwifery Students who Completed a Conflict Resolution and Resilience Building Workshop - Simpson, Naomi; Vernon, Rachael; Briley, Annette; Steen, Mary (Innovations in Pedagogy and Technology, 2025)
Midwifery is recognised as having a culture of workplace bullying. Bullying impacts midwives and midwifery students. Experiencing workplace bullying has negative consequences for midwifery students (professionally and personally). Developing midwifery students’ skills to manage conflict and maintain their well-being is important. We aimed to explore midwifery students' experiences of a bespoke education program to develop skills in conflict resolution, build resilience, and identify self-care strategies. This study was the second phase of an explanatory sequential mixed-methods research project. Twelve second-year midwifery students were interviewed between February and December 2024. Students had the option of attending an interview in person, by phone, or online (via Microsoft Teams/Zoom). Braun and Clarke’s six-phase framework was utilised to undertake a reflexive thematic data analysis. A previously published research protocol guided this study. Results demonstrated that participants perceived an improvement in their knowledge and understanding of workplace bullying, following workshop attendance. Upon reflection, the students acknowledged that their confidence in addressing bullying behaviour was still evolving. Several students described their resilience levels as improved and recognised the importance of good support in building individual resilience. Conflict resolution education appeared to be beneficial for midwifery students and enabled them to develop skills to identify and manage workplace bullying. Incorporating a bespoke educational workshop on conflict resolution into a Bachelor of midwifery degree, with subsequent reminder sessions, may improve students’ knowledge, ability, and confidence to manage workplace bullying. This education could also enable students to build resilience to deal with such conflict, which may improve workplace culture.